Monitoring of Kolka Glacier in 2014–2017 by terrestrial stereophotogrammetry - K. A. Aristov; D. A. Petrakov; N. V. Kovalenko; S. A. Timonin; A. A. Kolchin; V. N. Drobyshev (Лëд и снег)
The Kolka Glacier, which rushed down the Genaldon valley on September 20, 2002 (North Ossetia), is now recovering after this catastrophe. One of the most important ways to predict a new disaster is to determine the rate of ice accumulation of the new glacier and to monitor the glacier volume regularly, since its trigger mechanisms have not yet been fully studied. Recent changes of the Kolka Glacier were investigated by means of ground stereoscopic photography. The field works were carried out in 2014, 2016 and 2017. Shooting was made manually with a digital camera Canon 5D Mark II (without using a tripod) at arbitrary points, the distance between which did not exceed 100 m. The reference points were placed on the elevated relief forms on the glacier surface and coordinated by a differential GNSS receiver in the "fast static" mode. Laboratory processing of the photos was performed using Agisoft Photoscan software in automatic mode, except for the procedure of identification of reference points on stereo images. The processing made possible to obtain digital models of the glacier surface in Geo-TIFF format, the vertical error of which amounted to 0.7 m, while the horizontal one – 2.3 m. In 2014–2017, the maximal increase in height of the surface (up to 30 m) was recorded in the low part of the glacier tongue that was the result of advancing of the Kolka front along the ice-free surface. Mean annual increase in the surface elevation was equal to 2.2 m/year. Lowering of the surface in some areas may be explained by the slowing-down of the glacier flow rate, which led to the appearance of thermokarst. The glacier volume increased by 7.4±0.7 million m3. As a result, the glacier tongue advanced by 50–70 m. Average over 2014–2017 increasing in the surface elevation (2.2 m/year) was slightly smaller than in 2004–2014 (3 m/year). Quick growth of the Kolka Gacier contrasts sharply with decreasing of volume of the representative Caucasus, Djankuat and Garabashi, over the same period.